Relações dialógicas em revista infantil : processo de adultização de meninas - Ferreguett, Cristhiane (2014)
Nowadays the children live in a society with strong consumer appeal and since they are bombarded by advertising, they early develop the desire to buy superfluous goods that in their imagination will have the power to transform their life in a much better way. In this context, lipsticks, eye shadows, nail polishes, clothes and shoes appropriate for adult women are offered for very young girls as if these things were necessary for them. In the present research we analyze printed reports, which circulated in a special magazine called Recreio Girls, whose target audience is girls from six to eleven years. From the amount of five copies of this magazine, we selected three pieces of advertisment to make up the corpus of this research. The overall objective is to analyze how the advertising discourse is engendered in the discursive building of reports of the mentioned magazine and what effects of meaning are produced in relation to early adultization of girls. The study starts with considerations about the child in a socio-historical perspective and develops reflections on mass communication, general advertising and advertising to children, including also a discussion of the specific legislation. As a theoretical background, the research is supported in the assumptions of the Bakhtin Circle. The analyses are developed qualitatively by observing the various verbal and verbal-visual elements that constitute the selected reports. From such analysis, it is concluded that the reports show several characteristics of advertising discourse, such as presenting brands and product prices. It was observed that there has been a commitment of the speaker to approach the children and to gain their trust through using a change of tone to achieve his goal, sometimes performing as a child speaker, sometimes as an adult who wants to - apparently - take care and protect the children. Early adultization of girls is discursively constructed and can be seen through the strategy to present adults as reference models to girls, showing how they should choose what to dress , how they should wear makeup , have their hair combed as well as how they should behave and be. We also acknowledged that all advertising inserts in the analyzed reports disobey the Code of Consumer Protection (CDC) and the Code of Advertising Self-Regulation of Conar. From this study, one comes to the thesis that the advertising discourse, not completely explicit, engenders in different discursive materialities and encourages, through verbal and non-verbal utterances, the process of early adultization of girls, in order to promote and encourage the consumption of products that in fact are unnecessary for a child.